Clinical, histological, and biochemical predictors of postsurgical neuropathic pain. Issue 11 (November 2015) - Martinez, Valéria; Üçeyler, Nurcan; Ben Ammar, Skander; Alvarez, Jean-Claude; Gaudot, Fabrice; Sommer, Claudia; Bouhassira, Didier; Fletcher, Dominique
Abstract : Abstract: Surgical nerve injury sometimes leads to chronic postsurgical neuropathic pain (CPSNP). The risk factors for this condition are not well understood. We prospectively assessed 46 patients scheduled for iliac crest bone harvest, 2 days (D2) and 3 months (M3) after surgery, to determine the time course of nerve fiber degeneration and expression of the TNF-α and NGF genes in skin punch biopsies. Mechanical and thermal detection and pain thresholds were evaluated at D2 and M3, by quantitative sensory testing. Skin punch biopsies were also obtained from the thighs ipsilateral and contralateral to iliac crest bone harvest. Intraepidermal nerve fiber density (IENFD) and cutaneous TNF-α and NGF gene expression were analyzed. Forty-five volunteers matched for age, sex, skin color were examined as controls. Chronic postsurgical neuropathic pain was defined as pain in an area of hypesthesia with a positive Douleur Neuropathique 4 questionnaire score. Overall, 73% (N = 32) of patients developed hypesthesia and 40% (N = 13) of these patients had developed CPSNP at M3. Quantitative sensory testing results, IENFD, and skin TNF-α and NGF gene expression at D2 and M3 did not differ between patients with and without CPSNP. However, in patients with CPSNP, burning, compression, and pain provoked by brushing were correlated with IENFD at M3, suggesting a possible association between partial nerve lesions and more intense CPSNP, than with total nerve lesion. Furthermore, preoperative pain and opioid use were higher in patients who developed CPSNP than in those without CPSNP. These findings suggest that the predictors of CPSNP development are clinical rather than histological or biochemical. Abstract : Neuropathic pain severity is inversely correlated with small nerve fiber loss, but not with TNF-α and NGF gene expression, after iliac crest bone harvest.